Pengaruh Iklim Organisasi dan Burnout terhadap Kinerja Perawat RSUD Dr. Doris Sylvanus Palangka Raya - Asi, Sri Pahalendang (Universitas Brawijaya, Indonesia, 2013)
This study aimed to determine the effect of organizational climate and the performance of nurse burnout. This study uses descriptive analytic cross sectional approach. The research subjects are 106 nurses serving in inpatient installation dr. Doris Sylvanus Palangka Raya. Organizational climate was measured using a modification of organizational climate questionnare (OCQ). Burnout was measured using a modification of modified maslach burnout inventory (MBI). Instrument using 5 point Likert scale. Analysis of the test data used path analysis to find the relationship between organizational climate, burnout and performance, with the help of the program AMOS.6. The results showed that organizational climate significantly negative effect on burnout. Organizational climate has a significant positive effect on the performance of nurses. Burnout has a significantly negative effect on the performance of nurses. There is no direct effect of organizational climate on the performance of nurses through burnout.